Inclusão de estudantes com deficiência na educação superior: efeitos na docência universitária - Pieczkowski, Tania Mara Zancanaro (2014)
This thesis is inserted into the Special Education Research Line, of the Postgraduate Program in Education, at the Federal University of Santa Maria. It aims to tension the inclusion policy of students with disabilities in higher education, and understand the effects of this process in university teaching, this study was guided by the following research question: What are the effects of the inclusion of students with disabilities in university teaching? From this question, new questions derived, namely: What movements related to inclusion happen in the university, at present? What are the challenges of the teaching profession in the context of inclusion of students with disabilities? How do the processes of the teaching subjectivity, arising from policies of inclusion of people with disabilities in higher education happen? What are the effects of the presence of students with disabilities in the educational practices of university professors? The motivation for the choice of the research topic arises from my career in special education added to the challenge of being a teacher educator of future teachers, active in higher education, especially in undergraduate courses and in the teaching formation for higher education. For this study, acting teachers or teacher who worked with students with disabilities in different undergraduate courses in two universities of Santa Catarina, located in Chapecó SC were interviewed. The empirical data generated through narrative interviews was examined from the perspective of discourse analysis, supported by foucauldian references. I have taken the inclusion as a political practice of governmentality and that associated with the exclusion, are also incorporated in the economic game of a neoliberal State. The thesis I developed is that the presence of students with disabilities take effect on the university teaching, leading the way of being a professor, in other words, the teaching practices and the way of conceiving teaching. Teachers are captured by the discourses of inclusion, translated into standardization processes and effects of subjectivity. The meeting with the students with disabilities allows the teacher to reflect on the discourses often reproduced mechanically, as if it were natural, inevitable and necessary. Teaching the "different" is a chance for the distinct areas of professional active in the higher education knowledge find out that even dominating the specific content and earning academic degrees is not enough, since teaching is another profession, it is the meeting with the new, with the unpredictable. In accordance with Foucault's perspective, and operating with notions of discourse, governmentality, standardization and subjectivity, we did not intend to weave value judgments or point the right way, however, show the true effects created by the policies of inclusion.